Risk Factors for Retransplant Kidney Recipients: Relisting and Outcomes From Patients' Primary Transplant. Issue 6 (14th April 2014) - Heaphy, E. L. G.; Poggio, E. D.; Flechner, S. M.; Goldfarb, D. A.; Askar, M.; Fatica, R.; Srinivas, T. R.; Schold, J. D.
<x xml:space="preserve">Abstract</x> As of November 2013, 14.5% of the waitlist for a donor kidney comprised patients awaiting a retransplant. We performed a retrospective cohort study of 11 698 adult solitary kidney recipients using national Scientific Registry of Transplant Recipients data transplanted between 2002 and 2011. The aim was to investigate whether outcomes from patients' initial transplants are significant risk factors for patients' repeat transplants or for likelihood of relisting after a failed primary transplant. Retransplant recipients were more likely to be treated for acute rejection [adjusted odds ratio (AOR), 95% confidence interval (CI) = 1.26 (1.07–1.48), p = 0.0053] or hospitalized (AOR = 1.19, 95% CI 1.08–1.31, p = 0.0005) within a year of retransplantation if these outcomes were experienced within a year of primary transplant. Delayed graft function following primary transplants was associated with 35% increased likelihood of recurrence (AOR = 1.35, 95% CI = 1.18–1.54, p < 0.0001). An increase in 1‐year GFR after primary transplant was associated with GFR 1 year postretransplant (β = 6.82, p < 0.0001), and retransplant graft failure was inversely associated with 1‐year primary transplant GFR (adjusted hazard ratio = 0.74, 95% CI = 0.71–0.76 per 10 mL/min/1.73 m2). A decreased likelihood for relisting was associated with hospitalization and higher GFR following primary transplantation. The increasing numbers of individuals requiring retransplants highlights the importance of incorporating prior transplant outcomes data to better inform relisting decisions and prognosticating retransplant outcomes.